An Efficient Optical Mura Compensation System for Large Liquid-Crystal Display Panels - Zhang, Yao; Mao, Jianxu; Wang, Yaonan; Caiping, Liu; Zhang, Hui; Tan, Haoran; Wu, Haotian (IEEE transactions on instrumentation and measurement, 2022)
Increased mura defect rates as liquid-crystal display (LCD) sizes and resolutions increase have become an issue of the utmost concern for large LCD panel makers. To address this issue, an efficient optical mura compensation (referred to as a de-mura) system for large LCD panels is proposed in this work. More specifically, the following measures were implemented to ensure the operation of the system with high reliability and efficiency: 1) an elliptic paraboloid (EP) model was proposed to deal with the measurement error caused by the viewing-angle vignetting in the LCD panel during imaging; 2) a time-domain filter and other preprocessing algorithms were built into the firmware of a high-resolution monochrome camera; 3) to accurately compensate for luminance mura, a fourth-order polynomial was applied to generate luminance de-mura data and on this basis, a local linear interpolation model was established to generate the chromaticity de-mura data; and 4) the parallel acceleration of the algorithm was achieved by using a combined central processing unit (CPU) multithreading-graphic processing unit (GPU) computing architecture. The experimental results show that the developed system and algorithm perform quite well, in terms of reliability and operational efficiency. The tact time (TT) for 4K and 8K LCD panels was less than 20 and 25 s, respectively, which fully meets manufacturers' mass production requirements.